Novel use of a continuous PECS II block for mastitis pain treatment. Issue 7 (4th May 2020) - Delfino, Enrica; Netto, Roberta; Cena, Alessandra; Faraoni, Lorella; Gogna, Daniela; Montagnani, Luca
Abstract : Nipple trauma and mastitis (an inflammatory condition of the breast) are common causes of intense pain during breast feeding. Although such pain normally results in early weaning, which has negative impacts on both maternal and child health, little is understood about the treatment of pain experienced during breast feeding. Here, we describe our experience with a woman who presented at 26 days post partum with a 15-day history of deep nipple wounds that caused bilateral mastitis and excruciating pain that radiated dorsally. Antibiotic, antifungal and non-pharmacological therapies were unsuccessful, and she wished to suspend breast feeding. We performed a bilateral pectoralis nerve block type II and inserted intrafascial catheters between the pectoralis minor and serratus muscles for continuous analgesia. Following block completion, the pain in her torso resolved immediately. The local anesthetic infusion continued for 40 hours and the patient had sustained analgesia with rapid healing of nipple lesions and her breast feeding commencing at 36 hours after block placement.